A report on the proposal for using capital budgeting to study the performance of Digicity (M) Sdn. Bhd / Noor Maslidaini Mohammad - Mohammad, Noor Maslidaini (Faculty of Business and Management, 2009)
Capital budgeting is a very useful managerial tool that financial analysts can use to support business making by using, thorough, contextual information about a potential capital investment. In his/her duty as a financial manager he/she is to choose investments with satisfactory cash flows and rates of return. Therefore, a financial manager must be able to decide whether an investment is worth undertaking and be able to choose intelligently between two or more alternatives. The focus of this study is to propose the usage of capital budgeting approaches to evaluate the performance of a company being studied i.e. Digicity (M) Sdn Bhd in term of its profit or loss. It uses two different methods namely, Net Present Value and Internal Rate of Return which had been widely accepted as accurate methods. For the purpose of the study, the researcher evaluates one of the projects that the company has undertaken that lasted four years with a company called Formates Sdn Bhd from 2004 to 2008. Based on the data available the capital budgeting methods was used to calculate the NPV and IRR. Then for the same project, the researcher made a comparison of the profit margin obtained by using cost evaluation method. At the end of the study the advantages and disadvantages of the capital budgeting method was discussed, and the researcher believed that the usage of capital budgeting method would be a very useful decision-making tool for a medium size company like Digicity in carrying out its business.